Answer:
[tex]f(x)=-\frac{1}{12}(x-3)^2(x+2)^2(x-4)[/tex]
Step-by-step explanation:
The standard form for a polynomial equation in its factored form is:
[tex]f(x)=a(x-p)(x-q)...[/tex]
Where p and q are the zeros and a is the leading coefficient.
We know that the degree of the polynomial is 5.
We are also given roots at x=3 and x=-2. Hence, our factors are (x-3) and (x+2).
These have a multiplicity of two, so we will square them.
We also know that there is a root at x=4. Hence, the factor is (x-4). This has a multiplicity of 1.
Therefore, our polynomial is now:
[tex]f(x)=a(x-3)^2(x+2)^2(x-4)[/tex]
We know that the y-intercept is 12. Therefore, if we substitute in 0 for x, we should get 12 for y. Here, we are solving for our a. Therefore:
[tex]12=a(0-3)^2(0+2)^2(0-4)[/tex]
Evaluate:
[tex]12=a(9)(4)(-4)[/tex]
Evaluate:
[tex]-144a=12[/tex]
Divide both sides by -144:
[tex]a=-1/12[/tex]
Hence, our entire polynomial is:
[tex]f(x)=-\frac{1}{12}(x-3)^2(x+2)^2(x-4)[/tex]